MANAGEMENT MODEL OF A GENERAL SECONDARY EDUCATION INSTITUTION IN THE CONDITIONS OF MIXED EDUCATION - Virolainen, Oksana (International Journal of Innovative Technologies in Social Science, 2022)
The article analyzes the management and organizational-pedagogical foundations of the introduction of blended learning in an institution of general secondary education. A management model of a general secondary education institution in the context of the implementation of mixed education has been built. The proposed management model of a general secondary education institution contributes to the individualization of the educational process, encourages teaching staff to continuous self-education, promotes the formation of an information culture in them, sets them up for mastering innovative means of obtaining and applying information, and creating an individual educational trajectory. The organization of mixed education in institutions of general secondary education is gaining special relevance in extraordinary conditions, in particular a global pandemic, martial law in Ukraine [1]. The purpose and task of managing a general secondary education institution in the context of the implementation of mixed education is outlined. The management organization system of an educational institution, as a social phenomenon, is considered in several aspects: the study of the management conditions of a general secondary education institution in the conditions of the implementation of mixed education; determination of the index of cognitive activity of pedagogical workers of the institution of general secondary education in the conditions of mixed education; determination of the level of management efficiency of a general secondary education institution in the context of the implementation of mixed education.